Oat beta-glucan reduces colitis by promoting autophagy flux in intestinal epithelial cells via EPHB6-TFEB axis - Xu, Mingyang; Ling, Fangmei; Li, Junrong; Chen, Yidong; Li, Shuang; Cheng, Yiyu; Zhu, Liangru (Frontiers in Pharmacology, 2023)
Inflammatory bowel disease (IBD) is a group of chronic inflammatory disorders of the gastrointestinal tract, mainly including Crohn’s disease and ulcerative colitis. Epidemiological findings suggest that inadequate dietary fibers intake may be a risk factor for IBD. Oat beta-glucan is a type of fermentable dietary fiber and has been proved to reduce experimental colitis. However, the mechanism remains unclear. The aim of this study was to explore the role and possible mechanism of oat beta-glucan in reducing experimental colitis. We used a dextran sulfate sodium (DSS)-induced mice acute colitis model to explore the potential mechanism of oat beta-glucan in reducing experimental colitis. As a result, oat beta-glucan upregulated the expressions of Erythropoietin-producing hepatocyte receptor B6 (EPHB6) and transcription factor EB (TFEB), promoted autophagy flux and downregulated the expressions of interleukin 1 beta (IL-1β), interleukin 6 (IL-6) and tumor necrosis factor alpha (TNF-α) in intestinal epithelial cells (IECs). The role of the EPHB6-TFEB axis was explored using a lipopolysaccharide-induced HT-29 cells inflammation model. The results revealed that EPHB6 regulated the expression of TFEB, and knockdown of EPHB6 decreased the protein level of TFEB. When EPHB6 or TFEB was knocked down, autophagy flux was inhibited, and the anti-inflammatory effect of sodium butyrate, a main metabolite of oat beta-glucan in the gut, was blocked. In summary, our findings demonstrated that oat beta-glucan reduced DSS-induced acute colitis in mice, promoted autophagy flux via EPHB6-TFEB axis and downregulated the expressions of IL-1β, IL-6 and TNF-α in IECs, and this effect may be mediated by butyrate.